Reassessment of the non‐titanosaurian somphospondylan Wintonotitan wattsi (Dinosauria: Sauropoda: Titanosauriformes) from the mid‐Cretaceous Winton Formation, Queensland, Australia. (12th November 2014) - Poropat, Stephen F.; Mannion, Philip D.; Upchurch, Paul; Hocknull, Scott A.; Kear, Benjamin P.; Elliott, David A.; Benson, Roger
Abstract Wintonotitan wattsi, a Cretaceous titanosauriform sauropod from central Queensland, Australia, is redescribed following a full revision of its osteology. The holotype specimen, a partial postcranial skeleton derived from the lower Upper Cretaceous Winton Formation, comprises axial and appendicular elements. Wintonotitan has been commonly resolved as a non‐titanosaurian somphospondylan titanosauriform since its description, in contrast to its more derived contemporary Diamantinasaurus matildae. We provide a detailed redescription, taking this opportunity to correct four misinterpretations made in the original description of Wintonotitan that impact on our understanding of this taxon: the right ulna was originally described as the left and vice versa; the left metacarpus was incorrectly described as being from the right side; metacarpal IV was described as metacarpal V and vice versa; and the ilium was incorrectly oriented. The reassessment of the metacarpus is particularly important, since it shows that a proximal fossa is present on metacarpals I, II and III, which might have been occupied by either the strongly convex distal end of the radius or a (possibly unossified) carpal element. We provide a review of titanosauriform metacarpal morphology to support our reassessments. Our revision of the osteology of Wintonotitan results in the identification of several previously unrecognized autapomorphies, augmenting and revising its original diagnosis. We provide additional support for the previous referral of four caudal vertebrae from south‐east of Winton, Queensland, to W. wattsi. Furthermore, we demonstrate that a tentative report of titanosaur osteoderms from the Winton Formation was based on misidentification of dorsal vertebral neural spines pertaining to the holotype of W. wattsi. Consequently, titanosaur osteoderms are currently unknown from Australia. Following our revision and reinterpretation of a number of elements, we re‐examine the phylogenetic placement of Wintonotitan, supporting its position as a non‐titanosaurian somphospondylan titanosauriform, with no close relationship with the contemporaneous lithostrotian titanosaur Diamantinasaurus.